2018
DOI: 10.1111/joim.12823
|View full text |Cite
|
Sign up to set email alerts
|

Influence of anti‐inflammatory diet and smoking on mortality and survival in men and women: two prospective cohort studies

Abstract: Adherence to a diet with high anti-inflammatory potential may reduce all-cause, CVD and cancer mortality and prolong survival time especially amongst smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
30
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 63 publications
5
30
0
3
Order By: Relevance
“…Obesity, type 2 diabetes, and other metabolic disorders have a large impact on the health of society in Western and developing countries. These disorders not only increase the risk of cardiovascular disease; they also represent a common preventable cause of cancer (1, 2). Currently, about 15% of the world population suffers from obesity, 5–10% has type 2 diabetes, and these numbers are increasing (3, 4).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity, type 2 diabetes, and other metabolic disorders have a large impact on the health of society in Western and developing countries. These disorders not only increase the risk of cardiovascular disease; they also represent a common preventable cause of cancer (1, 2). Currently, about 15% of the world population suffers from obesity, 5–10% has type 2 diabetes, and these numbers are increasing (3, 4).…”
Section: Introductionmentioning
confidence: 99%
“…We observed that the average hsCRP among people with low AIDI was 1.0 mg/L as compared with 1.8 mg/L among those with high AIDI 15. Adherence to a diet with a high AIDI score was inversely associated with cardiovascular (CVD) mortality and was associated with increased survival time in a population-based prospective cohort of Swedish men and women 16. Until now, the anti-inflammatory potential of diet has not been examined in relation to specific types of CVD, including AAA.…”
Section: Introductionmentioning
confidence: 90%
“…Following stratification by sex, the association between the anti-inflammatory diet index and cancer mortality was significant only amongst men. In addition, the observed associations were strongest amongst current smokers [1]. This manuscript indubitably provides important and striking informations, and we would like to take this opportunity to share some additional thoughts and to partake our considerations.…”
mentioning
confidence: 90%
“…Dear Sir, In their very significant and well-presented large, population-based prospective cohort study entitled 'Influence of anti-inflammatory diet and smoking on mortality and survival in men and women: two prospective cohort studies' recently published in the Journal of Internal Medicine [1], Kaluza et al examined the associations between an anti-inflammatory diet index and all-cause and cause-specific mortality, determined the association between the anti-inflammatory diet index and differences in survival time and assessed effect modification by smoking status. [1]. The results showed that adherence to a diet with high anti-inflammatory potential was associated with increased survival time and lower all-cause, cardiovascular disease and cancer mortality.…”
mentioning
confidence: 99%